West Nile Virus, an Underdiagnosed Cause of Acute Fever of Unknown Origin and Neurological Disease among Hospitalized Patients in South Africa - Caitlin MacIntyre; Carla Lourens; Adriano Mendes; Maryke de Villiers; Theunis Avenant; Nicolette M. du Plessis; Fabian H. Leendertz; Marietjie Venter (Viruses, 2023)
West Nile virus (WNV), a mosquito-borne flavivirus, is endemic to South Africa. However, its contribution to acute febrile and neurological disease in hospitalized patients in South Africa is unknown. This study examined two patient cohorts for WNV using molecular testing and IgM serology with confirmation of serological results by viral neutralization tests (VNT) to address this knowledge gap. Univariate analysis was performed using collected demographic and clinical information to identify risk factors. In the first cohort, 219 cerebrospinal fluid (CSF) specimens from patients with acute neurological disease in Gauteng hospitals collected in January to June 2017 were tested for WNV. The study identified WNV in 8/219 (3.65%, 95.00% CI (1.59–7.07)) patients with unsolved neurological infections. The second cohort, from 2019 to 2021, included 441 patients enrolled between January and June with acute febrile or neurological disease from urban and rural sites in Gauteng and Mpumalanga provinces. West Nile virus was diagnosed in 40/441 (9.07%, 95.00% CI (6.73–12.12)) of patients, of which 29/40 (72.50%, 95.00% CI (56.11–85.40)) had neurological signs, including headaches, encephalitis, meningitis, and acute flaccid paralysis (AFP). Notably, most of the cases were identified in children although adolescents and senior adults had a significantly higher risk of testing WNV positive. This suggests a previously underestimated disease burden and that WNV might be underrecognized as a cause of febrile and neurological diseases in hospitalized patients in South Africa, especially in children. This emphasizes the importance of further research and awareness regarding arboviruses of public health concern.